A content analysis of an advanced level EFL coursebook concerning environmental education - Veszelinov, Eszter (Working Papers in Language Pedagogy, 2024)
The present research was conducted to evaluate an EFL coursebook in terms of its suitability for environmental education in Hungarian secondary schools. The coursebook chosen for this quantitative analysis was the English File advanced level coursebook, selected for the widespread use of the series. Both the student’s book and the workbook were investigated. One of the main aims of the study was to examine the range and frequency of environmental issues included in the coursebook. The other aim was to investigate the portrayal of some environmentally high-stakes behaviours in the coursebook in order to explore what behavioural models they provide for students. The topics of mobility and eating out were selected for analysis, due to their salience in the coursebook and for their heavy environmental impact. Content analytical methods were used for the study. Content related to environmental issues was revealed to be minimal, at less than 1%, as well as being limited in scope. In terms of mobility and eating out, the environmentally most harmful behaviours were found to be heavily overrepresented. The findings suggest that the coursebook fails to meet the aims of environmental education set by UNESCO and by the Hungarian Educational Authority. The findings are expected to inform future course material designers, as well as urge teachers to evaluate coursebooks critically in terms of environmental education.